Responding to Loneliness: Counselling the Elderly - France, M. Honoré (Canadian Journal of Counselling and Psychotherapy, 2011)
The purpose of this article is to provide a step-by-step description of the developmentand implementation of a group on Responding to Loneliness for the elderly."Responding to Loneliness" focuses on five main areas: building positive self-esteem;learning social and personal skills; managing stress and anxiety; developing problem solvingstrategies; and building a social network. The underlying assumption of thisgroup approach is that everyone is alone and is responsible for what is done about it.